2019
DOI: 10.24843/ejmunud.2019.v08.i11.p18
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kualitas Pelayanan, Kualitas Produk, Dan Inovasi Produk Terhadap Kepuasan Untuk Meningkatkan Loyalitas Pelanggan

Abstract: Kepuasan pelanggan merupakan faktor penting dalam menumbuhkan loyalitas pelanggan serta upaya yang tepat untuk menciptakan pengembangan perusahaan dalam jangka panjang. Kepuasan dapat tercipta ketika perusahaan berhasil memenuhi harapan dari konsumen yang kemudian akan menurunkan peluang keinginan pelanggan untuk beralih ke produk atau perusahaan lain, sehingga loyalitas pelanggan juga dapat terbentuk. Tujuan penelitian ini untuk menjelaskan pengaruh kualitas pelayanan, kualitas produk, dan inovasi produk terh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
5
0
2
Order By: Relevance
“…Nafisa & Sukresna (2018) also showed that there is a positive influence between customer satisfaction and customer loyalty. Then, Fauzi & Mandala (2019), Seesaiprai (2016), and YuSheng & Ibrahim (2019) also showed that customer satisfaction has a positive and significant influence on customer loyalty. Izogo & Ogba (2014) further explained that in order to gain customer loyalty to the car repair service industry, the company needs to improve customer satisfaction through improving the quality of service provided.…”
Section: The Effect Of Customer Satisfaction On Customer Loyaltymentioning
confidence: 98%
“…Nafisa & Sukresna (2018) also showed that there is a positive influence between customer satisfaction and customer loyalty. Then, Fauzi & Mandala (2019), Seesaiprai (2016), and YuSheng & Ibrahim (2019) also showed that customer satisfaction has a positive and significant influence on customer loyalty. Izogo & Ogba (2014) further explained that in order to gain customer loyalty to the car repair service industry, the company needs to improve customer satisfaction through improving the quality of service provided.…”
Section: The Effect Of Customer Satisfaction On Customer Loyaltymentioning
confidence: 98%
“…Demikian halnya dengan hasil penelitian lain yang dilakukan oleh Fauzi & Mandala tentang pengaruh kualitas pelayanan, kualitas produk, dan inovasi produk terhadap kepuasan untuk meningkatkan loyalitas pelanggan di Denpasar. Hasil penelitian tersebut menunjukkan kualitas pelayanan berpengaruh pada kepuasan pelanggan (Fauzi & Mandala, 2019).…”
Section: B Pengaruh Kualitas Layanan Terhadap Kepuasan Konsumenunclassified
“…Fauzi Muhammad & Mandala (2019) states that Relative advantage is the characteristic form of an old product against a new product that has been replaced to achieve the potential success of a product. To achieve consistency in product innovation, companies need to devote their time, resources, and efforts to the innovation.…”
Section: ) Relative Advantagementioning
confidence: 99%
“…To answer this question, the aspect of customer satisfaction must still be considered, to achieve convenience, companies still maintain and need to give their time, resources, and efforts to achieve the success of smartphone companies (Panigrahi et al, 2021). The significant effect of relative advantage on user technology acceptance has been reported by previous studies including (Panigrahi et al, 2021), andFauzi Muhammad &Mandala (2019), and (Dachi, 2020).…”
Section: ) Relative Advantagementioning
confidence: 99%